Integration of information-seeking skills and activities into a problem-based curriculum. - Schilling, K (1995)
Recent trends in medical education include a shift from the traditional, didactic, lecture-oriented approach to a more student-driven, problem-based approach to learning. This trend provides librarians with an opportunity to develop programs to teach information-gathering skills that support and are integrated into problem-based learning (PBL). In 1992, the University of Pittsburgh School of Medicine implemented the initial phase of a curriculum revision that emphasizes PBL. Since that time, Falk Library of the Health Sciences has provided a large-scale, intensive program integrating information-seeking skills and activities into the first-year Patient-Doctor Relationship course, a sequence that initiates medical school. A multimodal approach to information seeking and sources is emphasized, utilizing print and audiovisual materials, computerized resources, and subject experts. The Falk Library program emphasizes the gathering and use of information as central to both PBL and student skills development. An informal, post-course evaluation was conducted to gauge which information resources were used and valued most by students. This article presents evaluation results, including data on the use of information sources and services, and student perceptions of the librarian's role in the PBL sessions.